Butterflies of two atlantic forest conservation units from Paraíba state, northeast of Brazil - Gualberto, Emanoel Pereira; Medeiros, Adalberto Dantas de; Kerpel, Solange Maria (EntomoBrasilis, 2024)
Conservation Units are areas legally established by the government with the goal of conserving territory and its natural resources. Given the limited knowledge about the invertebrate biodiversity in the Northern Atlantic Forest, including its legally protected areas, the present study aimed to inventory butterfly species in two Conservation Units of the Northern Atlantic Forest in Paraíba, Brazil: Engenho Gargaú Private Natural Heritage Reserve (RPPN Gargaú) and Mata do Xém-xém State Park (PE Xém-xém), both located in the metropolitan region of João Pessoa. We conducted the collections every two months, over three consecutive days, in six expeditions from February 2013 to April 2014 in RPPN Gargaú and in four expeditions from August 2014 to April 2015 in PE Xém-xem. Additionally, a two-day collecting expedition was carried out in August 2021 in RPPN Gargaú. We employed two sampling methods: Van Someren-Rydon traps and entomological nets. A total of 212 species (2,841 specimens) were recorded, 158 (1,867 specimens) in RPPN Gargaú and 129 (974 specimens) in PE Xém-xém. Overall, Hesperiidae was the richest family (81 spp.), followed by Nymphalidae (70), Riodinidae (22), Lycaenidae (22), Pieridae (12), and Papilionidae (4). Out of the total species, 48 are new records for Paraíba, and seven for northeast Brazil. Notably, the record of Morpho menelaus eberti Weber, 1963 in RPPN Gargaú, a subspecies classified as Critically Endangered (CR), stands out. The results emphasize the need to protect the forest remnants in the region, as well as to develop management and monitoring actions for butterflies and other invertebrates.